The Intervening Role Of E-Customer Satisfaction: E-Service Quality And E-Trust Features Towards E-Customer Loyalty: Study of Mobile Banking Users in Jakarta - Muhammad Rafi Awlia; Fani Firmansyah (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
The main problem addressed in this research lies in understanding how E-Service Quality and E-Trust influence E-Customer Satisfaction and the extent to which these factors contribute to customer loyalty in the context of mobile banking.  This study seeks to examine the influence of E-Service Quality and E-Trust on E-Customer Satisfaction among BNI Mobile Banking users, with E-Customer Loyalty acting as an intervening variable. The study utilizes a descriptive quantitative approach and is conducted in Central Jakarta. A questionnaire employing a five-point Likert scale serves as the instrument for data collection, involving a total sample size of 105 participants. The results indicate that trust and satisfaction play a significant role in shaping loyalty, demonstrating that strong trust in electronic services enhances customer loyalty, while customer satisfaction mediates the relationship between electronic service quality and loyalty. Notably, the correlation between electronic service quality and customer satisfaction appears to be insignificant. The implications of these findings are critical for bank marketers and service providers in developing strategies to enhance trust and improve customer satisfaction. By prioritizing trust-building measures and addressing customer satisfaction effectively, banks can foster stronger loyalty among users, ultimately leading to improved retention rates and business performance in the competitive mobile banking landscape.